2018
DOI: 10.2474/trol.13.248
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Cutting Fluid Sterilized by Atmospheric-Pressure Plasma Treatment

Abstract: Plasma jet sterilization of cutting fluid was performed under atmospheric pressure, and the tribological properties of the resulting fluid were investigated. The mechanisms of atmospheric-pressure plasma jet sterilization were also clarified. The number of bacterial colonies in the sterilized fluid was reduced by more than 90% compared with the untreated fluid. After exposure to ultraviolet light, no comparable reduction was observed. We concluded that the sterilization observed in the study was caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The UV light generated by the plasma may therefore play an additional role in sterilization. As a result of examining the influence of UV sterilization, we found that UV rays do not affect sterilization under the experimental conditions used in the present work (Miyamoto et al, 2018). We concluded that the sterilization observed in the study was caused by the reaction of excited N 2 , NO, OH, and Ar.…”
Section: Resultssupporting
confidence: 46%
See 4 more Smart Citations
“…The UV light generated by the plasma may therefore play an additional role in sterilization. As a result of examining the influence of UV sterilization, we found that UV rays do not affect sterilization under the experimental conditions used in the present work (Miyamoto et al, 2018). We concluded that the sterilization observed in the study was caused by the reaction of excited N 2 , NO, OH, and Ar.…”
Section: Resultssupporting
confidence: 46%
“…The friction coefficient of the cutting fluids was investigated using a rotating tribometer. The measurement results of the friction coefficient are shown in the previous report (Miyamoto et al, 2018). The sample material was SKH51 (JIS G 4403) tool steel with a diameter of 30 mm and thickness of 10 mm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations